2017
DOI: 10.1093/infdis/jix632
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Influenza Vaccine Effectiveness: A Systematic Review, Meta-analysis, and Meta-regression of Test-Negative Design Case-Control Studies

Abstract: Exploration of new influenza vaccination strategies must be a priority for influenza control, particularly in tropical countries with year-round influenza virus activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 41 publications
0
97
0
1
Order By: Relevance
“…Exploring how gene expression changes with age in immune related genes can help further characterize the disease and improve treatments. For example, age, preexisting health conditions and influenza history (previous infection or vaccination) are all factors that can affect the efficacy of the vaccine (50). There is an on-going effort to improve efficacy of vaccination in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring how gene expression changes with age in immune related genes can help further characterize the disease and improve treatments. For example, age, preexisting health conditions and influenza history (previous infection or vaccination) are all factors that can affect the efficacy of the vaccine (50). There is an on-going effort to improve efficacy of vaccination in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…Potential confounders included the year of the surveillance program, participant's age and ethnicity, type of BMT intake, history of smoking and asthma (including childhood asthma), and receipt of influenza vaccine before the FRI episode. Assessment of whether the participant received MIV or TIV was based on self-reported vaccination history up to 1 year prior to the first FRI episode (since antibody titers and vaccine effectiveness could wane thereafter [17][18][19]), supplemented with Singapore Armed Forces records for vaccines received after enlistment. Since FRI episodes are concentrated differentially during a BMT course, we adjusted for this effect using the FRI incidence rate during successive 2-weekly phases after the time of enlistment for that intake type ( Figure 1B and Supplementary Materials).…”
Section: Study Design Outcomes and Exposures Of Interest Potential mentioning
confidence: 99%
“…Based on the antigenic distance hypothesis put forth by Smith et al, negative or positive interference can result from prior season vaccination depending on differences in the antigenic distances between prior and current vaccine strains and the current epidemic strain [7]. Most studies to date incorporated only a single previous season when examining the impact of repeated vaccination [8][9][10][11][12][13]. Meta-analyses of these studies found substantial heterogeneity in repeated vaccination effects [14][15][16].…”
Section: Introductionmentioning
confidence: 99%